A photonic frequency octo-tupler with reduced RF drive power and extended spurious sideband suppression. (July 2016) - Hasan, Mehedi; Hall, Trevor J.
Abstract: A Mach-Zehnder interferometer with each arm containing a pair of Mach-Zehnder modulators (MZM) in series is proposed as a means of optoelectronic frequency multiplication (octo-tupling and 24-tupling). All harmonics including the carrier are suppressed except those with order equal to an odd multiple of four. The circuit requires no electrical or optical filters. There is no requirement to carefully adjust the modulation index to achieve correct operation of the octo-tupler. A transfer matrix representation is used to describe the operation of the architecture. The theoretical predictions are validated by simulations performed using an industry standard software tool. The simulations also allow an assessment of the impact on the circuit operation of deviations from the ideal of its components such as the finite extinction ratio of the MZMs, power imbalances and phase error at the couplers and phase error of the applied RF signals. Finally, a comparison is made with an alternative functionally equivalent single-stage parallel MZM circuit. One finding is that the intrinsic conversion efficiency of the proposed circuit is improved by 3 dB over the alternative. The proposed circuit is suitable for integration in material platforms supporting linear electro-optic modulation such as LiNbO3, silicon, III–V or hybrid technology. Highlights: Required RF power is 3 dB less than previously reported equivalent parallel stage. The circuit can be functioned over a wide range of modulation index (2.0–7.30). There is no requirement of DC-bias or filter to suppress unwanted harmonics. Same circuit can be used for frequency 24-tupling adjusting modulation index.